Pengaruh Kepemimpinan dan Model Pembelajaran terhadap Keberhasilan Gerakan 7 Kebiasaan di SDN 1 Berkat - Halimah Halimah; Syarwani Ahmad (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the influence of principal leadership and teacher learning models on the success of the “7 Habits of Great Indonesian Children” movement at SDN 1 Berkat. This movement is an initiative to build students’ character through positive habits such as being proactive, responsible, having a win-win mindset, and synergizing effectively with others. The study employed a quantitative approach with a correlational design to examine the relationships and effects between variables. The population consisted of all 45 teachers and school staff, who were selected using a total sampling technique. Data were collected through a Likert-scale questionnaire, observation, and documentation. The data were analyzed using multiple linear regression with the help of SPSS version 26. The results showed that both principal leadership and teacher learning models had a significant influence—individually and simultaneously—on the success of implementing the 7 Habits movement. Principal leadership contributed 48%, while learning models contributed 42%, with a combined influence of 73%. Effective leadership was found to foster a positive school culture, whereas innovative learning models strengthened students’ character formation during the learning process. The findings highlight the importance of synergy between visionary school leadership and contextual learning models in cultivating positive character values among elementary school students in a sustainable manner.